Analysis Of The Topic Of Complementary Effects Of Genes By Solving Genetic Issues - Oygul Rasulova (Euro Asian Journal Publishing, 2024)
This article provides information on the complementary effect of non-allelic genes. Due to the complementary effect of genes, phenotypic separation is observed in the ratios 9:3:3:1, 9:3:4, 9:6:1, 9:7. The transmission of characters in the offspring under the complementary effect of genes is clarified by solving and analyzing genetic issues.
Keywords: gene; complementary effect of genes; genetic issue; genotypic ratio